“Examine the Multi-Scattering Effect on the Detected Backscattering Photons By Cometary Molecules” - B. Kadhim, Alaa; N. Ismaeal, Ghosoon (Iraqi Journal of Science, 2023)
The effect of multiple scattering on the detected γ-photons at the surface of Hyakutake comet, which emitted from the radioisotope 137Cs were studied and compared the results with the single scattering case. Also the multiple scattering results were gathered with the single scattering case and investigate the effect. The calculations were conducted to analyze the variation of counts rate with source detector separation and the source of energy. Monte Carlo (MC) method was used to simulate the scattering and absorption of photons in semi-infinite material by developing the program in FORTRAN language (77 - 90) for this purpose. The distance between the source and the detector takes values of 1, 2,….5 cm, the results showed that single scattering gives a maximum counts generally at distances between 3 and 4 cm, while the multiple scattering case appears increasing as the source detector distance increased.